Enhancing Interferometric SAR Performance over Sandy Areas: Experience from the TanDEM-X Mission - Martone, Michele; Braeutigam, Benjamin; Rizzoli, Paola; Yague-Martinez, Nestor; Krieger, Gerhard (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2016)
The TanDEM-X mission is served by two X-band synthetic aperture radar (SAR) satellites, which fly in close orbit formation acting as a large and flexible single-pass radar interferometer. The primary goal of the mission is the creation of a consistent and global digital elevation model (DEM). A very good and reproducible performance has been verified for most of the land masses. In this paper, a detailed performance analysis of TanDEM-X data is presented for sandy desert areas, which show a strong impact on the quality of spaceborne SAR surveys. The influence of several acquisition parameters on SAR and interferometric (InSAR) performance is evaluated by means of statistical analyses as well as long-term repeated acquisitions on defined test sites. Alternative processing approaches aiming at improving the quality of the interferometric products are presented, too. From the obtained analyses, a description of the scattering mechanisms occurring at X-band over sandy surfaces is derived, which allows to plan a dedicated reacquisition of such areas with optimized imaging geometry to improve the quality of the final TanDEM-X DEM.
DLR Import::2019-04-02
Keywords: Deserts; digital elevation model (DEM); performance; synthetic aperture radar interferometry (InSAR); TanDEM-X